Impact of Work Discipline, Compensation, and Job Satisfaction on Employee Performance at PDAM Kendal (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
The purpose of this research is to determine the effect of work discipline and compensation on employee performance with job satisfaction as an intervening variable at PDAM Tirto Panguripan, Kendal Regency. The population in this study were permanent employees of PDAM Kendal. Sampling in this research used probability sampling techniques. Data analysis and hypothesis testing in the research used the partial least squares structural equation method (PLS-SEM). Results of direct influence hypothesis testing using Smart PLS 4. The results show that work discipline has no significant effect on job satisfaction, compensation has a positive and significant effect on job satisfaction, job satisfaction has a positive effect on employee performance, work discipline has no significant effect on employee performance, compensation has an effect positive and significant on employee performance, work discipline has no significant effect on employee performance which is mediated by job satisfaction, and compensation has a positive and significant effect on employee performance which is mediated by job satisfaction.
Keywords: Work Dicipline; Compensation; Employee Perfomance; Job Satisfaction